FACTORS AFFECTING USER SATISFACTION IN BUSINESS ORGANIZATIONS AS PERCEIVED BY EMPLOYEES - Grace Orlyn Sitompul (Fakultas Ekonomi Universitas Advent Indonesia, 2019)
Previous studies on user satisfaction have revealed that it is influenced by several factors, such as technological variables, organizational variables, and user characteristics. The manner in which these factors interact with one another, directly or indirectly, in influencing User Satisfaction is not understood. The most significant of these factors affecting user satisfaction is also not established. We used Structural Equation Modelling in an attempt to determine which of several exogenous variables were significant. Online and face-to-face surveys were used (n=230) from Human Resource Information System users of selected business organizations in the Philippines and Indonesia. Top management support had an indirect effect on user satisfaction through technology ease of use (β = 0.773) and user skill (β = 0.165). Organizational culture (β = 0.253), technology ease of use (β = 0.490), and user skill (β = 0.165) had a direct effect on user satisfaction.